Luxuria and Homosexuality in Suetonius, Augustine, and Aquinas - Anagnostou-Laoutides, Eva (The Mediaeval Journal, 2015)
Abstract The article discusses Suetonius and the Stoics as two independent yet converging paradigms which shaped notions of morality and vice in late antiquity and influenced Augustine and his understanding of the vitium sodomiticum as luxury. Aquinas followed his definition with the implication that on this occasion he parted ways with his usual Aristotelian model, which appears much more lenient in discussing the vice of homosexuality.